Perancangan Sistem Manajemen Mutu Terintegrasi di Baristand Industri Padang - Yudo Purnomo; Nilda Tri Putri; Elita Amrina (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
Baristand Industri Padang is an agency under control Ministry of Industry of Indonesia which it has a duty to serve the industries involving research activities, standardization and certification. To realize the programs, Baristand Industri Padang implemented a quality management system including ISO 9001, ISO/IEC 17025, ISO/IEC 17065, and KNAPPP 02. Nevertheless, it has been running separately. Therefore, quality of products not only proven by testing the final product, but also needed other evidence as a certificate that ensuring the quality of products. This research aims to design the Quality Management System for Baristand Industri Padang which it was implemented using life cycle methodology. Finding of this study revealed there was integration of ISO 9001, ISO/IEC 17025, ISO/IEC 17065, and KNAPPP 02 in the context of the structure of the process, documents, and organization. In the context of the structure of processes, it obtained four groups of primary process involving management, research and standardization, support, and improvement. Moreover, In terms of documentation, there was three levels of the document such as the document of strategic policy, quality guideline and procedures. While aspects of the organizational structure, the integration of quality management system required to develop the organizational structure that consist of Top Management, Technical Manager, Quality/Management Representative, Researcher and Administrative/Technical Staff. In addition, this study provided an integrated quality management information system including management of quality documents and quality records. Finally, the integrated quality management system and quality management information system has been designed to meet the expectations of the organization.